Арифметика для малышей: стихи / Н. Владимирова - Владимирова Наталия (Для самых маленьких, 1999)
Экземпляры: аб. (2000) / Инвентарный номер: 42176 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: В 57 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5